Impact of fermentation temperature on required heat dissipation, growth and viability of yeast, on sensory characteristics and on the formation of volatiles in Riesling: Energy demand and volatiles during fermentation - Schwinn, Mira; Delgado, Antonio; Durner, Dominik; Wacker, Michael; Fischer, Ulrich (Australian Journal of Grape and Wine Research, 2019)
Background and Aims Temperature control during fermentation significantly impacts the energy demand of wineries. We determined the heat required to be dissipated from wine tanks under three different temperature programs (14, 16-11-17 and 19 degrees C) during 1200 L Riesling fermentations and investigated the influence of temperature on yeast growth and viability, the formation of yeast derived volatiles and wine sensory properties. Methods and Results Heat dissipated by the coolant was determined using heat meters. At 19 degrees C, similar to 70% less heat had to be dissipated compared to that at 14 degrees C, whereas similar to 30% less heat had to be dissipated for the 16-11-17 degrees C temperature program. The duration of fermentation was 15, 13 and 9 days for the 14, 16-11-17 and 19 degrees C programs, respectively. Characteristic profiles of heat dissipated per day and reduction in specific gravity were observed. The formation of most esters was more pronounced in the second half of fermentation at higher temperature. Hexyl acetate, however, was formed early and no temperature influence was observed. The final concentration of ethyl decanoate, ethyl octanoate and ethyl hexanoate was greater for fermentations at 19 degrees C, while that of ethyl butanoate was highest at 14 degrees C. No difference was found in the final concentration of acetate esters or acetic acid. Acetaldehyde concentration was 35% lower for fermentations at 19 degrees C, compared with those at 14 degrees C. Descriptive analysis, at 5 and 11 months after bottling, revealed no significant difference in wine sensory profiles. Flow cytometry showed faster yeast growth, greater population size and rapid viability decline at the higher fermentation temperature. Conclusions Energy savings can be achieved by reducing the required dissipated heat through temperature management of fermentations, without compromising wine composition. Ambient temperature should be considered when deciding on temperature management and related saving potentials. Significance of the Study Potential energy savings were demonstrated that may facilitate innovation in fermentation cooling systems.
CRIS-Team WoS Importer:2019-04-12
Keywords: energy saving; ester formation; fermentation; required heat dissipation; temperature management